2012
DOI: 10.1159/000339955
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms and Executive Functioning in Patients with Mild Cognitive Impairment: Relationship to Caregiver Burden

Abstract: Background: Caregivers of patients with mild cognitive impairment (MCI) need similar levels of support services as Alzheimer’s disease (AD) caregivers, but it is unclear if this translates to increased caregiver burden. Methods: 135 participants and their caregivers (40 MCI, 55 AD and 40 normal controls, NC) completed questionnaires, and the patients were administered neuropsychological tests. Results: The MCI caregivers reported significantly more overall caregiving burden than the NC, but less than the AD. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 48 publications
(47 reference statements)
3
29
3
1
Order By: Relevance
“…Thus, it is important to identify factors in the patient, the caregiver, and in the patient-caregiver relationship that create greater vulnerability or resilience to the negative effects of caregiving. Previous research has indicated that declines in patients’ emotional functioning are strongly linked with increased psychological distress in caregivers [1416]. In addition, declines in patients’ emotional functioning can negatively impact the marital relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to identify factors in the patient, the caregiver, and in the patient-caregiver relationship that create greater vulnerability or resilience to the negative effects of caregiving. Previous research has indicated that declines in patients’ emotional functioning are strongly linked with increased psychological distress in caregivers [1416]. In addition, declines in patients’ emotional functioning can negatively impact the marital relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Depression in AD is associated with several adverse consequences, including negative influences on the patients' quality of life and activities of daily living, early requirements for hospitalization, and increased caregiver burden [4,5,6,7]. In MCI patients, depression is associated not only with negative clinical impacts but also with an increased risk for conversion to AD [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Although Parkinson's disease (PD) is considered primarily a movement disorder [Reichmann et al, 2016], and Alzheimer's disease (AD) is generally construed as an escalating dementia [Geda, et al, 2013], it has become increasingly clear-and generally recognized-that the burden of accompanying neuropsychiatric disorders contribute to increased morbidity and mortality in these patients [Panza et al, 2015;Szeto and Lewis, 2016]. As such, these comorbidities add an additional burden on society [Ryan et al, 2012;Martinez-Martin et al, 2015] where, currently, the treatment of behavioral and psychological symptoms that accompany both AD and PD remains a challenge [Rabins and Lyketsos, 2007;Gauthier et al, 2010]. The current treatment strategies of these neuropsychiatric disorders mainly focus on agitation, aggression, delusions, and hallucinations [Rabins and Lyketsos, 2007;Soto et al, 2015].…”
Section: Introductionmentioning
confidence: 99%